Real user measurements : why the last mile is the relevant mile - Mastin, Pete (O'Reilly Media, 2016)
Real User Measurements (RUM) is gaining recognition as an effective way to monitor user interaction with your website or application, but there are quite a few misconceptions about what RUM is and how it works. In this O'Reilly report, you'll dive into the essence of this decades-old technology to learn why anything that can be measured can be measured with RUM. Author Pete Mastin from Cedexis also demonstrates how RUM can track facets that affect the quality of your web service, including page load times and latency. Mastin specifically focuses on the last mile: the ISP or network that connects end users to the Internet. That last mile is often the best place to improve performance, and RUM can help you determine how. Learn the pros and cons of implementing RUM--and how it compares to synthetic measurements Use RUM for both active and passive monitoring, as well as top-down and bottom-up monitoring Crowd-source results by aggregating RUM measurements from several web-driven companies Implement RUM on your site or app at the webserver, switch, or browser Examine several use cases where the last mile is important, and understand the complexities involved Compare Internet RUM with other forms of Real User Measurements to provide context and deeper understanding Pete Mastin, Director of Market Strategy and Product Evangelism at Cedexis, has years of experience in technology and business strategy. He has deep knowledge of IP Video, content delivery networks (CDN), and Internet and Cloud technologies.